Zaščita mahagonijevega lesa pred diskoloracijami - Tomažič, Miro (Les (Ljubljana), 2004)
The massive wood and plywood samples of African mahogany (Khaya sp.) were exposed to various illumination conditions. The largest changes of colour were exhibited after irradiation with UV light. As stated by FT-IR spectroscopy, exposure to UV light caused chemical changes of lignin and hemicellulose. In order to decrease the problem of fast discolourations of boat interior furniture elements, made of mahogany wood, already during production process, we tested preventive effectiveness of 17 different alkyd or acrylic polyurethane (PU) coatings. It was found out, that high sensitivity of PU coatings and PU finished mahogany plywood could be diminished by selection of appropriate UV-protecting additives. Although the protective coatings after application changed the colour of mahogany wood substantially, this remained relatively stable afterwards. Therefore, annoying discolorations of furniture made of mahogany wood do not appear during utilisation.
Keywords: les; mahagoni; razbarvanje